INNOVATIVE TEAMS THROUGH THE LENSES OF TEAM LEADERS: CHARACTERISTICS, CHALLENGES AND ACHIEVEMENTS - Nicoleta Dorina RACOLȚA-PAINA; Ileana MUNTEAN (Studia Universitatis Babeş-Bolyai Negotia, 2020)
Teamwork as well as the interest in innovation in business are two of the few constant features of contemporary companies, which manifest themselves within a general context characterized by volatility, uncertainty, complexity, and ambiguity. In a company, the benefits of teamwork are widely acknowledged, whereas innovation in business is a strategic direction. This work is based on empirical research, and its main purpose is to identify the characteristics of the innovative teams, the challenges that they have to face, and their achievements, respectively. The empirical research undertaken is a qualitative one and it proposes a case study, the primary data being collected through interviews conducted with a number of four team leaders of innovative teams. The respondents work for companies in the fields of production of electric/electronic products, information technology and computer services, GPS, navigation technology, respectively; all these are fields in which innovation is an important component of successful companies. According to the team leaders who were interviewed, the characteristics of the innovative teams can be assessed in terms of: (i) results (“deliverable”) which contribute to the general effort of the company to be competitive on the innovation market; (ii) performance (reaching efficiently all objectives), (iii) the way of working of the team (the presence of psychological safety, proper communication) and (iv) composition (the qualities of the team members, such as autonomy, diversity and orientation towards cooperation). The main challenge of the innovative teams is given by the high level of stress arising as a consequence of the conditions (such as deadlines and budget restrictions) under which the main objective has to be reached, namely, to obtain products and/or services, new or improved processes, respectively. To all of these, there can be added ones that are specific to teamwork, generally, such as existing conflicts, reduced motivation, and individualism at executive level. The main achievements of the innovative teams, according to the interviewed leaders, are the obtaining of new technologies, product optimisation, complying with deadlines, a high level of quality, and the employees’ development, which is an essential aspect which contributes to their motivation and implicitly to their training to become future leaders.